The toxic metal hypothesis for neurological disorders - Pamphlett, Roger; Bishop, David P. (Frontiers in Neurology, 2023)
Multiple sclerosis and the major sporadic neurogenerative disorders, amyotrophic lateral sclerosis, Parkinson disease, and Alzheimer disease are considered to have both genetic and environmental components. Advances have been made in finding genetic predispositions to these disorders, but it has been difficult to pin down environmental agents that trigger them. Environmental toxic metals have been implicated in neurological disorders, since human exposure to toxic metals is common from anthropogenic and natural sources, and toxic metals have damaging properties that are suspected to underlie many of these disorders. Questions remain, however, as to how toxic metals enter the nervous system, if one or combinations of metals are sufficient to precipitate disease, and how toxic metal exposure results in different patterns of neuronal and white matter loss. The hypothesis presented here is that damage to selective locus ceruleus neurons from toxic metals causes dysfunction of the blood–brain barrier. This allows circulating toxicants to enter astrocytes, from where they are transferred to, and damage, oligodendrocytes, and neurons. The type of neurological disorder that arises depends on (i) which locus ceruleus neurons are damaged, (ii) genetic variants that give rise to susceptibility to toxic metal uptake, cytotoxicity, or clearance, (iii) the age, frequency, and duration of toxicant exposure, and (iv) the uptake of various mixtures of toxic metals. Evidence supporting this hypothesis is presented, concentrating on studies that have examined the distribution of toxic metals in the human nervous system. Clinicopathological features shared between neurological disorders are listed that can be linked to toxic metals. Details are provided on how the hypothesis applies to multiple sclerosis and the major neurodegenerative disorders. Further avenues to explore the toxic metal hypothesis for neurological disorders are suggested. In conclusion, environmental toxic metals may play a part in several common neurological disorders. While further evidence to support this hypothesis is needed, to protect the nervous system it would be prudent to take steps to reduce environmental toxic metal pollution from industrial, mining, and manufacturing sources, and from the burning of fossil fuels.